Analisis Hubungan Keanekaragaman Mikroba Tanah dan Produktivitas Tanaman Padi pada Sistem Pertanian Organik dan Konvensional - Budi Santoso; Siti Rahmawati (Lembaga Publikasi Ilmiah Nusantara, 2026)
Soil microbial diversity plays a critical role in determining rice productivity through nutrient cycling, decomposition processes, and rhizosphere interactions. This study aims to analyze the relationship between soil microbial diversity and rice productivity under organic and conventional farming systems. A comparative approach was applied using empirical data from long-term studies that evaluated microbial communities and crop yield performance. The results indicate that organic systems exhibit higher microbial diversity, with a 15–35% increase in the Shannon diversity index compared to conventional systems. Functional microbial activities, including phosphate-solubilizing and nitrogen-fixing bacteria, were also higher under organic management. Rice productivity in organic systems showed greater long-term stability, although initial yields tended to be lower than those in conventional systems. Correlation analysis revealed a significant positive relationship between microbial diversity and crop yield (r = 0.72; p < 0.01). These findings highlight that soil microbiome management is a key factor in enhancing productivity and sustainability in rice farming systems.